2014
DOI: 10.1007/s12264-013-1412-1
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid biomarkers of Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is a fatal neurodegenerative disorder that takes about a decade to develop, making early diagnosis possible. Clinically, the diagnosis of AD is complicated, costly, and inaccurate, so it is urgent to fi nd specifi c biomarkers. Due to its multifactorial nature, a panel of biomarkers for the multiple pathologies of AD, such as cerebral amyloidogenesis, neuronal dysfunction, synapse loss, oxidative stress, and infl ammation, are most promising for accurate diagnosis. Highly sensitive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 93 publications
0
12
0
Order By: Relevance
“…Nevertheless, neuroinflammation and oxidative stress have received increasing attention as accumulating evidence suggests their involvement in its development [2,3]. Activation of microglia, the brain-specific macrophages, has been reported in both AD patients and animal models [4], accompanied by an activated complement system [5] and increased levels of chemokines and cytokines [6,7]. In addition, the protective effects of non-steroidal antiinflammatory drugs against AD risk [8] further support the neuroinflammation hypothesis of AD.…”
Section: Introductionmentioning
confidence: 95%
“…Nevertheless, neuroinflammation and oxidative stress have received increasing attention as accumulating evidence suggests their involvement in its development [2,3]. Activation of microglia, the brain-specific macrophages, has been reported in both AD patients and animal models [4], accompanied by an activated complement system [5] and increased levels of chemokines and cytokines [6,7]. In addition, the protective effects of non-steroidal antiinflammatory drugs against AD risk [8] further support the neuroinflammation hypothesis of AD.…”
Section: Introductionmentioning
confidence: 95%
“…However, the ‘gold standard’ peripheral biomarker for AD that will reliably identify individuals on a path toward AD, or even correlate with promising, but invasive and impractical cerebrospinal fluid (CSF) [2] and positron emission tomography (PET) biomarkers [3], is yet to emerge. Nevertheless, much hope is dedicated to the idea that such a marker does exist in the periphery.…”
Section: Introductionmentioning
confidence: 99%
“…The biomarkers that have been strongly associated with the diagnosis of Alzheimer's are Aβ-40, Aβ-42 and tau proteins [30][31][32][33][34][35]. All these biomarkers have been isolated from the cerebrospinal fluid and provide a fair estimation of Alzheimer's disease.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Hence, the focus for diagnosis of Alzheimer's has been shifted towards less invasive procedures. Assay of blood-based biomarkers has received great attention for the diagnosis and detection of Alzheimer's [30][31][32]. Studies have indicated that the plasma concentrations of Aβ-40 and Aβ-42 are high in individuals suffering from Alzheimer's.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation